2017
DOI: 10.1002/ana.24986
|View full text |Cite
|
Sign up to set email alerts
|

Timing is everything: Where status epilepticus treatment fails

Abstract: Status epilepticus is an emergency; however, prompt treatment of patients with status epilepticus is challenging. Clinical trials, such as the ESETT (Established Status Epilepticus Treatment Trial), compare effectiveness of antiepileptic medications, and rigorous examination of effectiveness of care delivery is similarly warranted. We reviewed the medical literature on observed deviations from guidelines, clinical significance, and initiatives to improve timely treatment. We found pervasive, substantial gaps b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 47 publications
2
60
0
2
Order By: Relevance
“…The number of published studies regarding delays in the treatment is relatively low [20] Nevertheless, results from the recent years show that delays in the treatment and compliance with suggested protocols are far from optimal, regarding both adults and paediatric patients [21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The number of published studies regarding delays in the treatment is relatively low [20] Nevertheless, results from the recent years show that delays in the treatment and compliance with suggested protocols are far from optimal, regarding both adults and paediatric patients [21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Una gran proporción de las urgencias neurológicas son tiempo-dependientes [3][4][5] , por esto se recomienda que "cualquier paciente con un problema neurológico urgente pueda ser atendido por un neurólogo en menos de una hora del inicio de los síntomas" 6 . Idealmente, en urgencias neurológicas de riesgo vital, la evaluación debiera realizarse dentro de 15 min desde el ingreso 6 .…”
Section: Discussionunclassified
“…Se asocian a un mayor riesgo vital y de secuelas, comparadas con otras emergencias médicas 2 . En muchas patologías neurológicas, como ataque cerebrovascular (ACV), meningitis bacteriana y status epilepticus, el diagnóstico rápido y certero es de suma importancia, debido a que el pronóstico depende de la velocidad con la que se inicie el tratamiento específico [3][4][5] .…”
unclassified
“…A literature review on observed deviations from guidelines found that > 30-min time to first-line treatment was present in 17-64% of patients, with the median time to first-line therapy being 30-70 min. Timing to first-line ASM was best explained by a delay in calling paramedics, and difficulty with administering rectal medication; delay to second-line therapy was attributed to inability of emergency medical services (EMS) to administer intravenous (IV) fosphenytoin; and variation in first-, second-, and third-line therapy may also be related to seizure detection and diagnostic difficulties [18]. Clinical assessment of pediatric SE treatment times found that the first ASM was administered at administration remain a matter of debate (Table 1).…”
Section: Variability In Treatment Protocolsmentioning
confidence: 99%
“…According to a review of 17 studies to assess divergences from recommended guidelines, 29-61% of patients were not following guidelines regarding drug choice, dosage, or sequence. In 23-49% of pediatric patients, there were more than two administrations of BZDs rather than the recommended escalation to a second-line drug, which may be associated with greater risk of respiratory depression [18]. Review of these studies shows that initial BZD dose was suboptimal in 19-68% of patients [32,33].…”
Section: Initial Benzodiazepine Dosingmentioning
confidence: 99%